Minimization of Makespan and Energy Consumption in Task Scheduling in Heterogeneous Cloud Environment - R. Priyadarshini; Mukil Alagirisamy; N. Rajendran; Arun Kumar Marandi; Vikas Vilasrao Patil; Vivek (International Journal of Intelligent Systems and Applications in Engineering, 2022)
In today’s IT industry, cloud computing is one of the technologies that is increasingly being used for regular corporate operations. The cloud is becoming more and more popular among businesses and research communities due to its many benefits, including on-demand self-service, quality of service, pay-per-usage pricing, virtualization, and elasticity. This research propose novel technique in makespan reduction with energy consumption for task scheduling. Here the cloud environment task scheduling for makespan reduction is carried out using gravitational grey wolf hybrid cuckoo scheduling. The simulation is suggested in the cloudsim programming environment, and the outcomes demonstrated the value of the energy-minimizing and makespan parameters. The simulation is suggested in the cloudsim programming environment, and the outcomes demonstrated the value of the energy-minimizing and makespan parameters. Proposed technique attained makespan of 67%, energy efficiency of 96%, execution speed of 79%, resource utilization of 63%, average waiting time of 66% for 500 number of tasks.